Microcrystalline diamond film evaluation by spectroscopic optical coherence tomography - Strąkowska, Paulina; Strąkowski, Marcin Robert (Photonics Letters of Poland, 2022)
This study has focused on the microcrystalline diamond film (MCD) thickness evaluation. For this purpose, optical coherence tomography (OCT) enhanced by spectroscopic analysis has been used as a method of choice. The average thickness of the tested layer was about 1.5 µm, which is below the standard 2-point OCT resolution. In this case, the usefulness of the spectroscopic analysis was confirmed for the evaluation of the thickness changes in the submicrometer range. Full Text: PDF References M.D. Drory, J.W. Hutchinson, "Diamond Coating of Titanium Alloys", Science, 263 (1994). CrossRef J. Wang, J. Zhou, H.Y. Long, Y.N. Xie, X.W. Zhang, H. Luo, Z.J. Deng, Q. Wei, Z.M. Yu, J. Zhang, Z.G. Tang, "Tribological, anti-corrosive properties and biocompatibility of the micro- and nano-crystalline diamond coated Ti6Al4V", Surf. Coat. Technol., 258 (2014). CrossRef P.A. Nistor, P.W. May, F. Tamagnini, A.D. Randall, M.A. Caldwell, "Long-term culture of pluripotent stem-cell-derived human neurons on diamond – A substrate for neurodegeneration research and therapy", Biomaterials, 61 (2015). CrossRef C.A. Love, R.B. Cook, T.J. Harvey, P.A. Dearnley, R.J.K. Wood, "Diamond like carbon coatings for potential application in biological implants—a review", Tribol. Int., 63 (2013). CrossRef P. Strąkowska, R. Beutner, M. Gnyba, A. Zielinski, D. Scharnweber, "Electrochemically assisted deposition of hydroxyapatite on Ti6Al4V substrates covered by CVD diamond films — Coating characterization and first cell biological results", Materials Science and Engineering: C, 59 (2016). CrossRef T.S. Ho, P. Yeh, C.C. Tsai, K.Y. Hsu, S.L. Huang., "Spectroscopic measurement of absorptive thin films by Spectral-Domain Optical Coherence Tomography", Opt. Express 22, 5 (2014). CrossRef N. Bosschaart, T.G. van Leeuwen, M.C.G. Aalders, D.J. Faber, "Quantitative comparison of analysis methods for spectroscopic optical coherence tomography", Biomedical Opt. Express 4, 11 (2013). CrossRef F.E Robles, C. Wilson, G. Grant, A. Wax, "Molecular imaging true-colour spectroscopic optical coherence tomography", Nat. Photonics 5, 12 (2011). CrossRef A.F. Fercher, W. Drexler, C.K. Hitzenberger, T. Lasser, "Optical coherence tomography - principles and applications", Rep. Prog. Phys. 66, 239 (2003). CrossRef A.M. Kamińska, M.R. Strąkowski, J. Pluciński, "Spectroscopic Optical Coherence Tomography for Thin Layer and Foil Measurements", Sensors 20, 19, (2020). CrossRef M. Kraszewski, M. Strąkowski, J. Pluciński, B.B. Kosmowski, "Spectral measurement of birefringence using particle swarm optimization analysis", Appl. Opt. 54, 1 (2015). CrossRef